MENINGKATKAN HASIL HAFALAN MELALUI MANAJEMEN KURIKULUM TAHFIDZ AL- QUR’AN - Yoni Afitasya Claritaningrum; Ida Faridah; Fitrohtul Khasanah (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the implementation of the Qur'an memorization program at MI TBS Al Fathonah, which is integrated into the school curriculum. The study uses a qualitative approach with data collection techniques through in-depth interviews with the principal and memorization teachers. The results show that the tahfidz program is implemented in a structured manner in teaching and learning activities (KBM) with an allocation of ten hours of lessons per week. Students are grouped into Grade A and Grade B based on their memorization abilities to improve learning effectiveness. The memorization method used is tailored to the abilities of the students, especially in lower grades, which still use the sima'i method (listening and imitating). The tahfidz program is also reinforced through daily murāja’ah practice, parental involvement, and a continuous assessment system through memorization tests and achievement books. The main obstacles faced are the limited number of tahfidz teachers and learning time that is divided with other flagship programs, adaptive methods, and collaboration between schools and parents.